Nanoparticles restore lysosomal acidification defects: Implications for Parkinson and other lysosomal-related diseases. Issue 3 (3rd March 2016) - Bourdenx, Mathieu; Daniel, Jonathan; Genin, Emilie; Soria, Federico N.; Blanchard-Desce, Mireille; Bezard, Erwan; Dehay, Benjamin
ABSTRACT: Lysosomal impairment causes lysosomal storage disorders (LSD) and is involved in pathogenesis of neurodegenerative diseases, notably Parkinson disease (PD). Strategies enhancing or restoring lysosomal-mediated degradation thus appear as tantalizing disease-modifying therapeutics. Here we demonstrate that poly(DL-lactide- co -glycolide) (PLGA) acidic nanoparticles (aNP) restore impaired lysosomal function in a series of toxin and genetic cellular models of PD, i.e. ATP13A2-mutant or depleted cells or glucocerebrosidase (GBA)-mutant cells, as well as in a genetic model of lysosomal-related myopathy. We show that PLGA-aNP are transported to the lysosome within 24 h, lower lysosomal pH and rescue chloroquine (CQ)-induced toxicity. Re-acidification of defective lysosomes following PLGA-aNP treatment restores lysosomal function in different pathological contexts. Finally, our results show that PLGA-aNP may be detected after intracerebral injection in neurons and attenuate PD-related neurodegeneration in vivo by mechanisms involving a rescue of compromised lysosomes.